Strategi Coping Stress Ibu yang Memiliki Peran Ganda Selama Pandemi Covid-19 - Elsya Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the research is what is the scope of stress experienced by mothers with dual roles during the Covid 19 pandemic. The research method uses qualitative research with a phenomenological design with an interview method. The participants used consisted of three women with the criteria of having a job and having school-age children. The results of this study are the scope of maternal stress with dual roles, namely (1). Stress in the family that is difficult to divide time, difficult to accompany children, decreased income and family problems; (2). Work stress is an increase in workload, adaptation to new work situations and a limited work environment. Mothers also experience symptoms of physical stress and symptoms of emotional stress. Coping used is Problem Focused Coping and Emotion Focused Coping, which is divided into adaptive coping and maladaptive coping. The conclusion of the study is that mothers with multiple roles experience stress from various aspects while carrying out their roles during the Covid-19 pandemic. Key Words: Coping Strategy, Coping Stress, School from Home, Two Role Mother